Estimation of Olibanum Effect on Blood Glucose, Oxidation, and Lipid Profile in Diabetes-Induced Rats - Gharb, Lamiaa A. (Iraqi Journal of Science, 2026)
This study was done at the Biotechnology Research Center/Al-Nahrain University to elucidate the activity of aqueous extract of olibanum after twenty days on glucose, lipids, and oxidation in diabetes-induced rats by using Alloxan (100 mg/kg). Twenty male rats aged 6 weeks and weighing 180±3g were categorised into four groups, five rats for each: group 1 (control) given distilled water, group 2: diabetic (no treatment), group 3: diabetic group given (150 mg\kg) of olibanum aqueous extract and group 4: healthy rats (non-diabetic) given aqueous extract. The results revealed that the rise in blood glucose was accompanied by an increase in triglycerides, cholesterol, very low-density lipoprotein, and low-density lipoprotein in diabetic rats. Groups 3 and 4 showed a significant decrease in blood glucose and ketone bodies. Also, the results showed an increase in insulin level on the 20th day of the experiment in group 3, and the levels of triglycerides, cholesterol, very low-density lipoprotein, and low-density lipoprotein decreased. Malondialdehyde showed a significant increase in group 2 compared to the control group and a decrease in group 3. Superoxide dismutase increased in groups 2 and 3 compared with control. Catalase enzyme value increased in the diabetic group compared with control, while in group 3 this value decreased with significant differences compared with the diabetic group. These results have shown that the consumption of olibanum aqueous extract has an important role in decreasing hyperglycemia, hyperlipidemia and free radicals.